Distress and Coping Strategy among Indonesian Men with Type-2 Diabetes Mellitus - Nugroho, Fajar Ari; Chandra, Rico Budhiarta; Laila, Nike; Rukia, Sera; Kusumastuty, Inggita; Cempaka, Anggun Rindang; Istifiani, Lola Ayu; Latif, Atifa Nafia Hasantie (Nurse Media Journal of Nursing, 2024)
Background: Type-2 diabetes mellitus (T2DM) can have a notable impact on the psychological and physical well-being of individuals, which in turn affects the management of the condition. Men and women experiencing stress and adopting distinct coping strategies. However, research focusing specifically on T2DM in men is still limited.Purpose: The present study intends to investigate the distress and coping strategies adopted by male T2DM outpatients in Malang, East Java, Indonesia.Methods: This study employed a qualitative research design and conducted in-depth interviews to 24 male T2DM outpatients. The interview guidelines were formulated using the Indonesian version of the Diabetes Distress Scale (DDS17) questionnaire, which comprised four domains: physician distress, emotional burden, regimen distress, and interpersonal distress. A thematic analysis was performed to analyze the results gathered during the research and compile them into a final report.Results: The study revealed that individuals diagnosed with T2DM experienced a range of emotional and practical difficulties, including feelings of fear, anxiety, and a lack of understanding. Disease burden, a lack of understanding of both diabetes and healthcare services, difficulties managing their diet, routine medication, financial concerns, and fatigue also contributed to the distress. To cope with distress, the informants identified eight distinct coping strategies. Of these, the most effective strategy was receiving support from family members, followed by acceptance, self management, positive attitude, understanding of their illness, joining the diabetes community, spirituality, and getting more information about T2DM.Conclusion: The findings of this study indicated that men experience eight distinct types of stress and utilise comparable coping strategies associated with T2DM. Emotional distress represents the predominant pressure, while family support constitutes the primary coping strategy. These results are important for nurses and other healthcare professionals in supporting patients.